2013
DOI: 10.7717/peerj.164
|View full text |Cite
|
Sign up to set email alerts
|

Using cloud-based mobile technology for assessment of competencies among medical students

Abstract: Valid, direct observation of medical student competency in clinical settings remains challenging and limits the opportunity to promote performance-based student advancement. The rationale for direct observation is to ascertain that students have acquired the core clinical competencies needed to care for patients. Too often student observation results in highly variable evaluations which are skewed by factors other than the student’s actual performance. Among the barriers to effective direct observation and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Mobile applications have also been employed for transparent and objective performance assessment and evaluation of medical students by their teachers. This includes performance in Objective Structured Clinical Examinations (OSCEs) and web-based courses [ 28 ]. In addition, mobile learning provides medical students a means to self-directed learning, an important tool in the medical practice where learning is continuous and life-long [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile applications have also been employed for transparent and objective performance assessment and evaluation of medical students by their teachers. This includes performance in Objective Structured Clinical Examinations (OSCEs) and web-based courses [ 28 ]. In addition, mobile learning provides medical students a means to self-directed learning, an important tool in the medical practice where learning is continuous and life-long [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that clinical skills are most efficiently attained through implementation of technologies such as e-learning and video recorded simulations, and real time patient simulation ( 4 - 7 ). It has also been shown that students tend to underestimate their abilities and feel unconfident about performing the acquired skills ( 8 ).…”
mentioning
confidence: 99%
“…In the end, a student must be evaluated by his performance. Ferenchick and Solomon have developed a mobile assessment tool (basically web based questionnaires) for observers to document proved student skills [ 76 ].…”
Section: Resultsmentioning
confidence: 99%